Exploring online teaching and learning challenges for the technical and vocational education and training lecturer - Mesuwini, Joseph; Mokoena, Sello (Journal of Education and e-Learning Research, 2024)
This paper explored the challenges lecturers face in teaching through online platforms. Online learning has become increasingly prevalent in Technical and Vocational Education and Training (TVET) institutions, offering opportunities and challenges for TVET lecturers. The transition from traditional face-to-face teaching to online environments requires lecturers to adapt to the new teaching methods, design engaging content, and navigate digital platforms. The qualitative research gathered data from 35 lecturers out of 60 conveniently and purposefully selected from five engineering campuses at a South African TVET college. Participants were accessible to the researcher and possessed online teaching experiences. Participant observation was used as a data-gathering tool. The study attempts to answer the question: What challenges are lecturers facing during online teaching and learning? The Technological Pedagogical Content Knowledge Framework for Teacher Knowledge by Koehler and Mishra guided the study. Data were analysed thematically from the identified patterns and themes. The findings revealed technical difficulties like connectivity and software glitches, which disrupted the teaching and learning process. Lecturers grappled with receiving practical online support. The limited interaction and collaboration among students in virtual settings posed additional challenges in maintaining engagement and addressing individual learning needs. Furthermore, access and equity issues hindered students' ability to participate fully due to inadequate technology, internet access, and power outages. To overcome these challenges, the study recommended lecturers continuous professional development in online learning methods and technologies. Addressing the challenges contributes to the successful implementation of online learning in the TVET sector by ensuring quality education and enhancing students' skills and competencies.